Introduction to the business of tourism - "Vasudevan, Venu; Vijayakumar, B" (New Delhi, 2017)
This textbook offers a lucid understanding of the business of tourism and helps students gain professional and entrepreneurial insights. An outcome of years of experience and practice, An Introduction to the Business of Tourism offers a fresh perspective of the skill-oriented, knowledge-based and multi-disciplinary arena of the tourism business. It presents a balanced mix of the basic principles and concepts, their application and policy implications as well as the business realities and operational aspects of the tourism industry. Divided into four sections and spread across nineteen chapters, this textbook delves deep into Indian and international tourism experiences with numerous integrated case studies and examples.
Keywords: Economics